Climate Risk Management for Agriculture Extension Curriculum Consultative Workshop in Ghana - List, Geneva; Hansen, James; Trzaska, Sylwia (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project aims to enhance access to climate information services (CIS) and validated climate-smart agriculture (CSA) technologies in Africa, to help these countries strengthen the resilience of their agricultural sectors to the threat posed by climate change. Strengthening the capacity of next users, particularly agricultural extension and advisory service (EAS) providers who work to support farmers in Ghana and five other target countries, is crucial for achieving this goal. Towards these ends, the AICCRA project has been working to co-design curricula targeting the agricultural extension systems in each of the six AICCRA target countries to build foundational knowledge and skills to manage climate risk. These curricula aim to help EAS providers to take advantage of best-available and location-specific climate information and tools in their countries to better plan for, manage, and respond to a changing and varying climate. They also aim to pragmatically support the tailoring and communication of such information to meaningfully inform on-farm agricultural decision-making and build wider resilience of the agricultural sector.